IMPLEMENTASI KEBIJAKAN PENDIDIKAN DASAR DAERAH KEPULAUAN ( Suatu studi di Kecamatan Manganitu Selatan Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara) - GIGHILE, PRISKILA NATALIA; TULUSAN, FEMMY; LONDA, VERY (Sam Ratulangi University, 2018)
Basic education in the area of the Sangihe Islands Regency, especially in Manganitu Selatan sub-district, hasconstraints in fulfilling educator resources in accordance with skills and expertise in the field, the deficiencyresulted in the program not running in accordance with the expected procedures and objectives.Implementation of this study aims to find out how the implementation or implementation of policies ineducation, especially primary school education in Southern Manganitu District, using descriptive qualitativeresearch methods. The results of this study indicate that, the fulfillment of educators or resources in SouthManganitu District is not in accordance with what is expected, proved in the study that the number of existingresources is not balanced with the number of primary school classes, the result of these shortcomings can affectthe learning system for students because every educator should be concurrent in teaching and not in accordancewith the abilities and areas they travel. Likewise in the existing financial management, as evidenced by the lackof facilities or facilities in school infrastructure is still lacking. Based on these conclusions, the researchersuggests that the resources of educators in Manganitu Selatan sub-district should be improved for thefulfillment of the quality and life of the next generation of the nation starting from the elementary school level,all forms of operational management must be implemented in accordance with established procedures forimplementation a policy that has been planned for the realization of a common goal.Keywords: Policy Implementation, Basic Education, Archipelago Region.